PENGARUH MODEL PEMBELAJARAN SAVI (SOMATIC, AUDITORY, VISUAL, INTELLECTUAL) TERHADAP HASIL BELAJAR IPA SISWA KELAS VIII SMP SWASTA YPI DHARMA BUDI KECAMATAN SIDAMANIK - Dianti Siboro, Thiur; Mustika Piliang, Fenny; Ariska, Windy (Program Studi Pendidikan Biologi, Fakultas Keguruan Dan Ilmu Pendidikan Universitas Simalungun, 2024)
This research aims to determine the effect of the SAVI (Somatic, Auditory, Visual, Intellectual) learning model on the science learning outcomes of class VIII students at YPI Dharma Budi Private Middle School, Sidamanik District, Academic Year 2023/2024. The population in this study were all class VIII students consisting of 2 classes with a total of 60 students. Sampling was carried out using non-probability sampling, saturated sampling or total sampling. Data analysis was carried out by determining the validity test, reliability test, linearity test, normality test, homogeneity test, R2 test, and hypothesis test, proven by the